Modulated Calcium Homeostasis and Release Events Under Atrial Fibrillation and Its Risk Factors: A Meta-Analysis - Fong, Sarah Pei Ting; Agrawal, Shaleka; Gong, Mengqi; Zhao, Jichao (Frontiers in Cardiovascular Medicine, 2021)
Background: Atrial fibrillation (AF) is associated with calcium (Ca2+) handling remodelling and increased spontaneous calcium release events (SCaEs). Nevertheless, its exact mechanism remains unclear, resulting in suboptimal primary and secondary preventative strategies. Methods: We searched the Pubmed database for studies that investigated the relationship between SCaEs and AF and/or its risk factors. Meta-analysis was used to examine the Ca2+ mechanisms involved in the primary and secondary AF preventative groups. Results: We included a total of 74 studies, out of the identified 446 publications from inception (1982) until 31 March 2020. 45 were primary and 29 were secondary prevention studies for AF. The main Ca2+ release events, calcium transient (standardised mean difference and spark amplitude were enhanced in the primary diseased group whilst calcium transient frequency was increased in the secondary group. Calcium spark frequency was elevated in both the primary diseased, and secondary AF groups. One of the key cardiac currents, the L-type calcium current, ICaL was significantly downregulated in primary diseased and secondary AF groups. Furthermore, the sodium-calcium exchanger (INCX) and NCX1 protein expression were significantly enhanced in the primary diseased group whilst only NCX1 protein expression was shown to increase in the secondary AF studies. The phosphorylation of the ryanodine receptor at S2808 (pRyR-S2808) was significantly elevated in both primary and secondary groups. It was increased in the primary diseased and proarrhythmic subgroups and secondary AF group. Sarco/endoplasmic reticulum Ca2+-ATPase (SERCA) expression was elevated in the primary diseased and proarrhythmic drug subgroups but substantially reduced in the secondary paroxysmal AF subgroup. Conclusions: Our study identified that ICaL is reduced in both primary and secondary diseased groups. Furthermore, pRyR-S2808 and NCX1 protein expression are enhanced. The remodelling leads to elevated Ca2+ functional activities, such as increased frequencies or amplitude of Ca2+ spark and Ca2+ transient. The main difference identified between primary and secondary diseased groups is SERCA expression which is elevated in the primary diseased group and substantially reduced in the secondary paroxysmal AF subgroup. We believe our study will add new evidence to AF mechanisms and treatment targets.